Interaction of JAK with steroid receptor function - Gupta, Nibedita; Mayer, Doris (JAK-STAT, 2013)
The function of steroid receptors is not only regulated by steroid hormones, but also by multiple cellular signaling cascades activated by membrane-bound receptors which are stimulated by growth factors or cytokines. Cross-talk between JAK and steroid receptors plays a central role in the regulation of a multitude of physiological processes and aberrant signaling is involved in the development of numerous diseases including cancer. In this review we provide a brief summary of the knowledge of interactions between JAK and the function of steroid receptors in normal cells and tissues and in diseases.